Application of M-matrices theory to numerical investigation of a nonlinear elliptic equation with an integral condition - Sapagovas, Mifodijus; Griškonienė, Viktorija; Štikonienė, Olga (Nonlinear Analysis: Modelling and Control, 2017)
The iterative methods to solve the system of the difference equations derived from the nonlinear elliptic equation with integral condition are considered. The convergence of these methods is proved using the properties of M-matrices, in particular, the regular splitting of an M-matrix. To our knowledge, the theory of M-matrices has not ever been applied to convergence of iterative methods for system of nonlinear difference equations. The main results for the convergence of the iterative methods are obtained by considering the structure of the spectrum of the two-dimensional difference operators with integral condition.*The research was partially supported by the Research Council of Lithuania (grant No. MIP-047/2014).
Keywords: elliptic equation; finite-difference method; integral boundary condition; iterative method; eigenvalue problem; M-matrix; regular splitting